We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
356
1
avatar

Solve for $r$: $\frac{r+9}{r-3} = \frac{r-2}{r+5}$

 Dec 30, 2017

Best Answer 

 #1
avatar+8437 
+1

\(\frac{r+9}{r-3}\,=\,\frac{r-2}{r+5}\)

 

Note that  r  cannot be  3  or  -5  since these values cause a zero in the denominator of the original equation. Now multiply both sides of the equation by  r - 3 , and multiply both sides by  r + 5 .

 

(r + 9)(r + 5)  =  (r - 2)(r - 3)

                                                  Multiply out the factors.

r2 + 14r + 45   =   r2 - 5r + 6

                                                  Subtract  r2  from both sides of the equation.

14r + 45  =  -5r + 6

                                                  Add  5r  to both sides.

19r + 45  =  6

                                                  Subtract  45  from both sides.

19r  =  -39

                                                  Divide both sides by  19 .

r  =  -39/19

 Dec 30, 2017
 #1
avatar+8437 
+1
Best Answer

\(\frac{r+9}{r-3}\,=\,\frac{r-2}{r+5}\)

 

Note that  r  cannot be  3  or  -5  since these values cause a zero in the denominator of the original equation. Now multiply both sides of the equation by  r - 3 , and multiply both sides by  r + 5 .

 

(r + 9)(r + 5)  =  (r - 2)(r - 3)

                                                  Multiply out the factors.

r2 + 14r + 45   =   r2 - 5r + 6

                                                  Subtract  r2  from both sides of the equation.

14r + 45  =  -5r + 6

                                                  Add  5r  to both sides.

19r + 45  =  6

                                                  Subtract  45  from both sides.

19r  =  -39

                                                  Divide both sides by  19 .

r  =  -39/19

hectictar Dec 30, 2017

8 Online Users